A new mechanism of symmetry of current-voltage characteristics for high-k dielectric capacitor structures - Lau, Wai Shing. (2013)
Historically, there has been a controversy regarding whether the leakage current versus voltage (I-V) relationship is governed by the Schottky mechanism or by the Poole-Frenkel (P-F) mechanism for several decades. For the P-F mechanism, the I-V characteristics is expected to be symmetrical. In this paper, the author points out that there is an extra mechanism for symmetrical I-V characteristics.